GENERIC DRUGS IN THE UNITED STATES: POLICIES TO ADDRESS PRICING AND COMPETITION - Gupta, Ravi (Clin Pharmacol Ther, 2019)
The cost of prescription drugs in the U.S. continues to be a source of concern for patients, caregivers, and policymakers. Drug prices typically decline rapidly once generic drugs receive U.S. Food and Drug Administration (FDA) approval and enter the market, but the past decade has witnessed rising costs and shortages of generic drugs. We describe the strategies employed by brand-name manufacturers to undermine generic competition and the reasons underlying the price increases of off-patent drugs, some of which continue to lack any competition from generic versions, and others that have increased in price despite having generic versions. We discuss the FDA’s role in addressing drug prices and promoting competition, including recent agency policies to modify its process of reviewing generic drug applications and prioritize applications for off-patent drugs with few competitors. We also examine proposed policy solutions and research areas that could help address the price increases of off-patent drugs.